Pengembangan Bahan Ajar Flipbook pada Mata Pelajaran IPS Siswa Kelas V Sekolah Dasar - Agustian, Dendi Albet; Erwandy, Rudi; Sofiarini, Andriana (IJOCE: Indonesia Journal of Civic Education, 2025)
This study aims to develop flipbook-based teaching materials for fifth-grade Social Studies learning that meet the criteria of validity, practicality, and effectiveness. The method used was Research and Development with the ADDIE development model. Data collection techniques included observation, interviews, questionnaires, and tests. The results showed that the developed flipbook teaching materials achieved a very high level of validity, with language expert validation at 92%, media expert validation at 86%, and content expert validation at 89%. The practicality assessment by teachers and students was categorized as very practical, with an average score of 92%. Furthermore, the effectiveness of the teaching materials was indicated by an average N-Gain score of 0.61, which falls into the moderate category. In conclusion, the flipbook-based teaching materials for Social Studies are proven to be valid, practical, and effective, making them suitable for use as an alternative learning resource to improve the quality of Social Studies instruction at the fifth-grade level. Keywords: Development, Flipbook Teaching Materials, Elementary School